The Effect of Vitamin B1 and Nano Zinc on Drip Irrigation Systems for Macakal Mangosteen (Garcinia mangostana) - Nurreni, Annisa; Susiyanti, Susiyanti; Hilal, Samsu; Sulistyorini, Endang (Jurnal Biologi Tropis, 2025)
The macakal mangosteen plant (Garcinia mangostana var. Macakal) is a plant that originates from Lebak Regency, Banten Province. Mangosteen plants experience slow growth due to their root system, which makes it difficult for them to absorb water and nutrients from the soil. Vitamin B1 is a substance that can stimulate plant tissue growth and development. The nutrient Zn functions to form hormones to achieve physiological balance. This study aims to determine the effect of vitamin B1 and nano zinc fertilizer application through a drip irrigation system on the growth of macakal mangosteen plants. This study was conducted from May to August 2023. It used a factorial randomized block design consisting of two factors. The first factor was vitamin B1 (V) (15 mg/l, 30 mg/l, and 45 mg/l), and the second factor was nano zinc fertilizer (T) (2 ml/l, 4 ml/l, and 6 ml/l). From these two factors, nine treatment combinations were obtained, and each treatment was repeated three times, resulting in 27 experimental units. The responses observed included Plant Height (cm), Stem Diameter (mm), Number of Leaves (pieces), Number of Branches, Leaf Length (cm), Leaf Width (cm), Leaf Length and Width Ratio (cm), and Leaf Greenness Level (chlorophyll units). The concentration of 45 mg/l of vitamin B1 had the best effect on the stem diameter parameter of 10.64 mm and the leaf greenness parameter of 69.81 units. The concentration of 2 ml/l of nano zinc fertilizer had the best effect on the plant height parameter of 43.50 cm. There is an interaction between vitamin B1 and nano zinc fertilizer on the number of leaves parameter, which is 16.33 leaves.